PENGARUH DISIPLIN KERJA, KEPEMIMPINAN, DAN MOTIVASI TERHADAP KINERJA PEGAWAI (Studi Pada PT. Telkom Semarang) - NIZAM NUR FAHMI, 14.05.51.0076; Kasmari, Kasmari (Students' Journal of Economic and Management, 2019)
This study aims to analyze the influence of work discipline, leadership, and motivation to employee performance PT. Telkom Semarang. Types of data used are primary data is data obtained directly from the original source in the form of a questionnaire. Population in this research is employees of PT. Telkom Semarang. Sampling was done by Purposive Sampling technique with a total sample of 105 respondents. The Data collected were analyzed using analysis factor to test the validity of the question items, the reliability testing using cronbach alpha and hypothesis testing using multiple linear regression. The test results obtained that there is a positive and significant influence of labor discipline on employee performance, there is a positive and significant influence of leadership on employee performance, there is a positive and significant influence of motivation on employee performance.